AMMONIUM-MODIFIED NATURAL ZEOLITE: A PROMISING CATALYST FOR RENEWABLE DIESEL PRODUCTION – A REVIEW - Putra, Riandy; Rosmainar, Lilis; Rasidah (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2025)
The global shift toward sustainable energy has intensified research into renewable diesel production, owing to its superior fuel properties and environmental benefits. Catalysts play a crucial role in the hydrodeoxygenation of vegetable oils and biomass-derived feedstocks to produce green diesel. Natural zeolites, valued for their high thermal stability and tunable acidity, have emerged as cost-effective catalytic alternatives. This review explored recent advancements in the application of ammonium-modified natural zeolites as catalysts in green diesel production. Characterization techniques, including FT-IR (Fourier Transform Infrared Spectroscopy), XRD (X-ray Diffraction), SEM (Scanning Electron Microscopy), TG-DTG (Thermogravimetric Analysis), nitrogen adsorption isotherms, and NH₃-TPD (Temperature-Programmed Desorption of Ammonia), were employed to analyze NH₄⁺-zeolites. Results demonstrate that ammonium modification enhanced the acidity, porosity, and catalytic efficiency of natural zeolites, leading to improved deoxygenation selectivity and increased green diesel yields. The NH₄⁺-modified zeolite achieved a C₁₅ hydrocarbon selectivity of 70%, compared to 54% for the unmodified variant. Furthermore, introducing ammonium ions helped regulate acidity by mitigating excessive Brønsted acidity, ultimately reducing coke formation and improving catalyst stability. This review discusses the physicochemical properties and catalytic performance of ammonium-modified natural zeolites in green diesel production. It also addresses the challenges and future directions for scaling up their application in renewable fuel technologies